Thelma and Louise - Ridley Scott (Norris spencer)
Actores: Susan Sarandon, Geena Davis, Harvey Keitel, Michael Madsen, Stephen Tobolowsky, Christopher McDonald, Brad Pitt.
Area-Película
Keywords: Genero-Drama